Концепция организации хранения данных для параллельного ввода-вывода в кластерных ВС - Вдовикин, О.И.; Машечкин, И.В. (Інститут програмних систем НАН України, 2004)
This work describes an approach to the high-performance parallel I/O management in the multiprocessor computing environments. The author proposes a way for development a file system that specifically addresses the requirements of computing clusters. The work contains experimental results of practical approbation of given approach and a discussion for future research directions.